Le réexamen des affaires du vol 007 de la Korean Airlines et du RB-50 (Note) - Ilyashov, Anatoli (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1994)
As revealed by documents in the National Archives in Washington, u.c., the United States routinely and knowingly sent reconnaissance flights over the Soviet Union during the fifties and sixties. The u-2 shootdown of the pilot Francis Gary Powers in 1960 was a manifestation of this dangerous pattern during the Cold War era. The author, the first Fulbright Lecturer to the formerly « closed-to-foreigners » military-industrial city of Nizhny Novgorod, or Gorki, suggests a direct correlation between this pattern of earlier reconnaissance flights and the shoot down of the KAL 007 airliner in 1983. It thus contains implications for current foreign policy in the bold new post-Cold War era, in which the means for surveillance have become more militarily sophisticated and technologically advanced.